PENGARUH EARNING PER SHARE, DEBT TO EQUITY RATIO, RETURN ON EQUITY, DAN CURRENT RATIO TERHADAP PRICE TO BOOK VALUE PERUSAHAAN SUB SEKTOR ADVERTISING PRINTING MEDIA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2017 - Mutiara Via Maudy; Deny Ismanto (Universitas Ahmad Dahlan, 2018)
This study aims to examine the effect of Earning Per Share, Debt To Equity Ratio, Return On Equity and Current Ratio to Price to Book Value on advertising printing media companies listed on the Indonesia Stock Exchange for the period 2014-2017. This research is descriptive quantitative research. The research population is all advertising printing media companies listed on the Indonesia Stock Exchange for the period 2014-2017 with a total of 15 companies. The sample selection was determined by purposive sampling technique with the criteria of the stock being sampled were the companies that published theirfinancial statements during the consecutive research year, so that samples are 12 companies were obtained. This study uses a statistical panel data regression analysis tool. The results of the study using Earning Per Share, Debt To Equity Ratio, Return On Equity and Current Ratio to Price to Book Value have results, the Debt To Equity Ratio variable affects the dependent variable Price to Book Value, while the other independent variables have no effect, that is; Earning Per Share, Return On Equity and Current Ratio. With the value of R Squared of 66.5% which explains the large influence on Price to Book Value.